The language of greeting gestures in traditional kazakh culture through the lens of contemporary visual anthropology (Journal of Philosophy, Culture and Political Science, 2025)
This study is based on the premise that the language of traditional gestures possesses a distinct specificity – both as an attribute of its semiosphere and as a bodily modality of “constituted behavior”, that is, a socially embedded program of corporeality. In this case, the focus is on traditional Kazakh society and its worldview. The research aims to examine the language of traditional Kazakh greeting gestures through the framework of visual anthropology. Gestures, as a form of embodied communication, are analyzed as a particular bodily modality within the holistic and contemplative worldview of a nomadic society. Engaging with traditional cultural practices – specifically, descriptions of Kazakh greeting gestures – does not preclude drawing on “indigenous knowledge”, which, within the Kazakh epistemological tradition, is referred to as “steppe knowledge”. Traditional gestures carry axiological significance, rooted in sacrality and linked to ritual practices as well as conceptions of the unified cosmos and the human body. The semiotic structure of greeting gestures is anchored in the sacred (magical) meanings ascribed to elements of the human body, understood as an emanation of the nomadic cosmos. The gendered dimension of traditional Kazakh greeting gestures functions as a regulatory code, structuring the system of social interaction. A key finding of this study, within the perspective of visual anthropology, is the recognition that analyzing gesture as a sign must also account for an equally fundamental, structural component of gesture language – corporeality as a mode of embodied cognition and image-based thought. The conclusions drawn from this research highlight the broader potential for studying gesture language as an object of cultural anthropology, semiotics, and communication studies, particularly within cross-cultural research on the sociology of the body.Keywords: traditional greeting gestures, gesture semiotics, visual anthropology, nomadic society, corporeality